Safety of intravenous immunoglobulin in the elderly treated for a dysimmune neuromuscular disease. Issue 5 (19th January 2016) - Lozeron, Pierre; Not, Adeline; Theaudin, Marie; Denier, Christian; Masnou, Pascal; Sarov, Mariana; Adam, Clovis; Cauquil, Cécile; Adams, David
ABSTRACT: Introduction: Many patients treated with intravenous immunoglobulin (IVIg) are >60 years of age. Tolerability has yet to be demonstrated in this age group. Methods: This is a retrospective study of adverse reactions among consecutive patients treated with IVIg for neurological disorders. Risk factors were recorded. Correlation and relative risks were calculated for age, risk factors, IVIg course, daily dose, concentration, preparation, and duration of treatment. An infusion and monitoring protocol was applied. Results: Two hundred forty‐four patients were reviewed, including 62% who were ≥60 years of age (total dose 1.8 ± 0.4 g/kg body weight, daily dose 30.3 ± 2.0 g). Sixty‐nine percent received sugar‐stabilized IVIg. Forty‐nine percent presented with >1 risk factor. Adverse reactions occurred in 35% and led to treatment discontinuation in 5%, with a similar incidence among age groups. In patients ≥60 years old, sucrose‐free IVIg administration was an independent predictor of adverse reactions, including renal failure. Conclusion: In the elderly, IVIg infusions are safe. Adverse reactions mainly depend on IVIg preparation and administration. Renal failure is not uncommon with sugar‐free IVIg. Muscle Nerve 53 : 683–689, 2016